2009
DOI: 10.1080/13691050802521155
|View full text |Cite
|
Sign up to set email alerts
|

Gender norms in South Africa: implications for HIV and pregnancy prevention among African and Indian women students at a South African tertiary institution

Abstract: In post-Apartheid South Africa, women are constitutionally guaranteed protections and freedoms that were previously unknown to them. These freedoms may have positive implications for women’s ability to negotiate sexual protection with partners and hence prevent unintended pregnancy and decrease their risk of HIV. Among tertiary institution students who are a relatively ‘privileged’ group, there is little information on gender norms that might shape responses to HIV prevention programmes. To elicit gender norms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 36 publications
1
41
0
Order By: Relevance
“…Over the past few decades, specifically in the developing nations, women have represented the fastest growing demographic of the HIV/ AIDS pandemic. Reports in the literature suggest that biological and socioeconomic vulnerability makes women at higher risk for HIV (3,4). The current methods of preventing HIV infection, such as abstinence, condoms, and monogamy, are frequently ineffective and often outside a woman's control (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past few decades, specifically in the developing nations, women have represented the fastest growing demographic of the HIV/ AIDS pandemic. Reports in the literature suggest that biological and socioeconomic vulnerability makes women at higher risk for HIV (3,4). The current methods of preventing HIV infection, such as abstinence, condoms, and monogamy, are frequently ineffective and often outside a woman's control (5).…”
Section: Introductionmentioning
confidence: 99%
“…The placebo gel used in the trial was the "universal" HEC placebo gel, which has been shown to have minimal anti-HIV activity (6). We hypothesize that our patented bioadhesive formulation (7), composed of two FDA-approved polymers, Pluronic® F-127 (polyoxyethylene polyoxypropylene co-polymer, polaxomer) and Noveon® AA-1 (polyacryclic acid), will [1] be a more efficacious platform for delivery of the antiviral drugs tenofovir and acyclovir, [2] offer protection against viral infection, and [3] have a long residence time because it will form micelle-like particles that adhere to the vaginal wall. The epithelium of the vagina contains glycogen, which is broken down by enzymes and bacteria into lactic acid to maintain low vaginal pH between 4 and 5, which is inhospitable to pathogens (8).…”
Section: Introductionmentioning
confidence: 99%
“…First, masculinities (and more broadly, gender) have been shown to be flexible in an African context (as elsewhere). A number of historical and political economic shifts have altered gender relations, including colonialism, apartheid, migrant labor, and urbanization (Hunter, 2004;Mantell et al, 2009;Morrell, 1998). In some ways, gender relations have moved toward greater gender equality.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies on the use of contraception in South Africa have presented conflicting reports implicating the husbands' or partners' disapproval of family planning and their unwillingness to use condoms as significant in the midst of other factors mediating non-use of birth control by the women [23][24][25] . Nonetheless, there is evidence that majority of Black men and women believe that the decision regarding the use of contraception is women's responsibility 18,26 .…”
Section: Introductionmentioning
confidence: 99%